Gas-lift wells optimization at the oil field "K" - Danilović Dušan; Ilić Marija; Crnogorac Miroslav; Tomić Lola (Podzemni Radovi, 2022)
Optimization the operating parameters of a group of gas-lift wells in an oil field is a complex procedure. It is important to match parameters such as gas compression pressure, gas injection pressure, separation pressure at the gathering station, diameters of distribution pipelines, injection gas quantities as well as all individual operating parameters of the gas-lift wells. In this paper, a model for determining the optimum gas injection rate was created. Also, it is described the procedure for gas-lift well optimization at the oil filed "K" and its results. For all five wells, the optimum amount of injected gas and required number of gas-lift valves were determined.